PENGGUNAAN COPULA ARCHIMEDEAN UNTUK PEMODELAN SEVERITY DAN FREKUENSI KLAIM ANTAR PERIODE PADA ASURANSI KENDARAAN BERMOTOR - YUSUF, FEBY INDRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Bivariate Archimedean Copula to modeling dependence between severity and frequency claims that have different marginal. Generalized Linear Model (GLM) was used as marginal model for the severity and frequency claims. Parameters joint copula can be estimated using maximum likelihood. These parameters results are used to obtain the prediction value of severity, frequency and policy loss insurance companies. The best model of Archimedean Copula family is determined by small grade MSE which is given by severity and frequency prediction